Gas‐Phase Unimolecular Dissociation Reveals Dominant Base Property of Protonated Homocysteine Sulfinyl Radical Ions. Issue 3 (4th November 2015) - Love‐Nkansah, Chasity B.; Tan, Lei; Francisco, Joseph S.; Xia, Yu
Abstract: Homocysteine sulfinyl radical ( SO⋅ Hcy) is a reactive intermediate involved during oxidative damage of DNA in the presence of high concentrations of homocysteine (Hcy). The short lifetime of SO⋅ Hcy makes its preparation, isolation, and characterization challenging using traditional chemical measurement tools. Herein, we demonstrate the first study on mass‐selected protonated SO⋅ Hcy ions in the gas phase by investigating its unimolecular dissociation pathways from low energy collision‐induced dissociation (CID). Tandem mass spectrometry (MS/MS), stable‐isotope labeling, and theoretical calculations were employed to rationalize the observed fragmentation pathways. The dominant dissociation channel of protonated SO⋅ Hcy was a charge‐directed H2 O loss from the protonated sulfinyl radical (‐SO⋅) moiety, forming a thiyl radical (‐S⋅), which further triggered sequential radical‐directed ⋅SH loss through multiple pathways. Compared to cysteine sulfinyl radical ( SO⋅ Cys), the small structural change induced by one additional methylene group in the side chain of SO⋅ Hcy significantly promotes its base property while reducing the radical reactivity of sulfinyl radical. This observation provides new insight into studying reactions of SO⋅ Hcy with biomolecules, which are critical in understanding toxicity induced by high levels of Hcy in biological conditions. Abstract : Homocysteine sulfinyl radical ( SO⋅ Hcy) is an under‐characterized intermediate resulting from oxidative damage of homocysteine. Herein, the intrinsic property of protonated SO⋅ Hcy ion is probed by studying its unimolecular dissociation in the gas phase. Experimental results complemented by theoretical calculations show that the flexible side chain of SO⋅ Hcy significantly promotes the base property of sulfinyl radical (‐SO⋅) while suppressing its radical property, which is distinct from cysteine sulfinyl radicals.